Using Walking Approaches and Site-Specific Performance to Reveal Layers of Feeling Attached to Place - Aled Singleton (GeoHumanities, 2025)
This paper aims to meet the desire for dynamic and multi-dimensional aspects of studying feelings attached to places. Starting with a contemporary example of a place in crisis and whose affective history seems linked to the 1984–85 UK miners’ strike, this paper argues for methodologies that avoid drawing straight lines from feelings attached to the past into the present-day. Rather than following dominant emotions, this work pursues Kathleen Stewart’s approach to ordinary affects: feelings that start and end in social worlds, but which are equally personal and intimate. A case study from Wales, UK, uses the creative mediums of walking tours and site-specific performances to bring the public into the research, which in turn helps to interpret feelings of the past revealed from 13 interviews focused on older people. This writing considers future methodological developments, such as focusing on younger people, encouraging local stakeholders as co-producers, and deepening artist collaborations.